Application of the Grain-Based Rock-Eval Pyrolysis Method to Evaluate Hydrocarbon Generation, Expulsion, and Retention of Lacustrine Shale - Liao, Lingling; Wang, Yunpeng; Chen, Chengsheng; Pan, Yinhua (Frontiers in Earth Science, 2022)
The study on hydrocarbon generation, expulsion and retention of shale is becoming more and more important as the exploration of unconventional oil and gas worldwide. There distribute a lot of lacustrine shales in the eastern area of China, which show great potential for shale oil/gas exploration. We proposed an effective method, namely grain-based Rock-Eval pyrolysis method, to evaluate hydrocarbon generation, expulsion and retention of shale. In this study, the grain-based Rock-Eval pyrolysis method was conducted on three sets of lacustrine shales including Nenjiang shale, Shahejie shale and Maoming oil shale. For comparison, pyrolysis of kerogens from three shale samples was also performed at the same conditions. Grains of Maoming oil shale showed a slightly broader distribution of activation energies than Nenjiang shale and Shahejie shale, while grains of Nenjiang shale showed higher dominant activation energy than Shahejie shale and Maoming oil shale. At laboratory heating rates (5–25 °C/min), the corresponding temperature to the maximum hydrocarbon generating rate of shale grains was collectively higher than its kerogen. Extrapolated to geological heating rate (3 °C/my), the corresponding maturity and geological temperature to the maximum hydrocarbon expulsion rate of grains from Maoming oil shale are earlier than both Nenjiang shale and Shahejie shale, while those for kerogens from Shahejie shale and Maoming oil shale are similar, earlier than kerogens from Nenjiang shale. At the earlier maturation stage (Ro = 1%), the retention proportions for Nenjiang shale, Shahejie shale and Maoming oil shale were estimated to 41.68%, 10.11% and 19.37%, respectively. At advanced maturation stage (Ro = 3%), the retention proportions for the three shales were changed to 39.01 %, 6.53% and 18.78%, respetively. These results suggested that Nenjiang shale from the Songliao Basin exhibits the strongest retention ability but the weakest expulsion ability, while Shahejie shale from the Dongying Depression shows the strongest expulsion ability but the weakest retention ability among the three samples. This study is expected to provide a quantitative frame in laboratory for evaluating hydrocarbon generation, expulsion and retention of shale.